2021
DOI: 10.5853/jos.2021.02446
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of Leptomeningeal Collaterals after Large Vessel Occlusion and Blood Pressure Management with Endovascular Treatment

Abstract: Endovascular therapy (EVT) is an effective treatment for ischemic stroke due to large vessel occlusion (LVO). Unlike intravenous thrombolysis, EVT enables visualization of the restoration of blood flow, also known as successful reperfusion in real time. However, until successful reperfusion is achieved, the survival of the ischemic brain is mainly dependent on blood flow from the leptomeningeal collaterals (LMC). It plays a critical role in maintaining tissue perfusion after LVO via pre-existing channels betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 104 publications
1
23
0
1
Order By: Relevance
“…After LVO, a significant drop in local perfusion pressure occurs within the affected vascular territory, cerebral autoregulatory mechanisms are unable to maintain adequate regional CBF, and the cardiac output now becomes the sole driving force of regional CBF. Since retrograde perfusion to the ischemic area via leptomeningeal anastomoses is dominant in most patients with LVO and the direction of blood flow through leptomeningeal anastomoses is determined by the perfusion pressure gradient, poor cardiac output would further result in reduced collateral flow perfusion 29 30. This is supported by our data, showing that patients with LVSD had a lower median ASITN/SIR grade (1, IQR 0–2 vs 3, IQR 1–3 in patients without LVSD, P<0.001) and a higher frequency of impaired collaterals (30 (75%) vs 68 (40%)) in patients without LVSD, P<0.001).…”
Section: Discussionsupporting
confidence: 72%
“…After LVO, a significant drop in local perfusion pressure occurs within the affected vascular territory, cerebral autoregulatory mechanisms are unable to maintain adequate regional CBF, and the cardiac output now becomes the sole driving force of regional CBF. Since retrograde perfusion to the ischemic area via leptomeningeal anastomoses is dominant in most patients with LVO and the direction of blood flow through leptomeningeal anastomoses is determined by the perfusion pressure gradient, poor cardiac output would further result in reduced collateral flow perfusion 29 30. This is supported by our data, showing that patients with LVSD had a lower median ASITN/SIR grade (1, IQR 0–2 vs 3, IQR 1–3 in patients without LVSD, P<0.001) and a higher frequency of impaired collaterals (30 (75%) vs 68 (40%)) in patients without LVSD, P<0.001).…”
Section: Discussionsupporting
confidence: 72%
“…Pathophysiological knowledge suggests that the direction of this independent relationship is that poor CC leads to increased BP. LVO causes a drop in perfusion pressure, which leads to recruitment and vasodilatation of the leptomeningeal collaterals and, due to impaired cerebral autoregulation, the direction and amount of blood flow through CC rely on systemic perfusion, which can be estimated by BP ( 18 ). Until successful reperfusion, the survival of hypoxemic brain tissue depends on CC flow, and for this reason guidelines do not recommend lowering BP unless it is extremely high ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, perfusion-based imaging is able to provide key information on cerebral blood perfusion by gathering parametric data on mean transit time (a marker of how long it takes blood to traverse a certain region) and cerebral blood volume (marker of amount of volume contained within a certain region). 18 Complex deconvolutional-based mathematical analysis of these parameters over the time course of image acquisition creates both a quantitative and qualitative graphical depiction of the ischemic core (critically hypoperfused area that is presumed to be infarcted), penumbra (partially hypoperfused area destined for death but potentially salvageable with reperfusion), and oligemic region (reduced flow but metabolically stable area). 19 Nevertheless, although these are very powerful techniques, they are indeed prone to inaccurate findings due to underlying mathematical assumptions of brain tissue physiology, namely, its permeability and time-contrast enhancement.…”
Section: Visualization Of Collateralsmentioning
confidence: 99%
“…As such, given that flow vectors are largely driven by pressure gradients within the collateral system, it becomes imperative to strictly regulate BPs in order to ensure collateral patency, limit cerebral edema, mitigate risk of hemorrhagic conversion, create a favorable environment for penumbral salvage, and improve overall functional outcomes. 18 Unfortunately, there is profound lack of dedicated randomized control trials to guide systemic BP management in stroke. Early trials have demonstrated a U-shaped relationship between systolic BP (SBP) at presentation following acute ischemic stroke and outcomes.…”
Section: Blood Pressure Managementmentioning
confidence: 99%